INITIATION OF THE DESA TANGGUH BENCANA THROUGH STIMULUS-RESPONSE METHOD - S. Maarif; F. Damayanti; E.D. Suryanti; A.P. Wicaksono (Indonesian Journal of Geography, 2012)
The model of “desa tangguh bencana” (disaster resilient village) has to be initiated throughstimulus program. Social values existed in local community are basic capital in establishingdisaster resilient village. Mapping the site properties and characteristics is an essential stepto capture the community’s level of vulnerability and capacity. Establishment of “desatangguh bencana” is one of methods to involve local community in community based disasterrisk reduction (CBDRR). The initiation of disaster resilient in Pagubugan Kulon was donethrough stimulus-response method to introduce safe and resilient culture. Building up thegood understanding of disasters becomes one important way to rise up the communitypreparedness. The community response in Pagubugan Kulon to the disaster stimuli is theestablishment of “desa tangguh bencana pratama”.